Differentiating Between Malaria and Dengue Fever Using Hematological Parameters in an Endemic Area - Pushpam, J Stephanie Lilia; Rai, Preethi; T, Umashankar; Noronha, Dotton Denis (Annals of Pathology and Laboratory Medicine, 2023)
Background Malaria and Dengue fever are the two most common arthropod-borne diseases in tropical countries like India, and endemic areas like Mangalore. Since they share a similar clinical presentation, identifying the hematological parameters, can help differentiate between patients of malaria and dengue fever and can help with its prognosis and early treatment. This study aims to find a link between diagnostic markers that are used to discriminate between the infections, occuring in malaria-endemic areas, such as Mangalore, Karnataka. Methods Retrospective study was carried out at department of Pathology, Father muller medical college, Mangalore for the duration of 2 years, January 2019 to January 2021. The hematological parameters for the diagnosed cases were collected from hospital database, were analyzed and evaluated. Results White blood cells, neutrophils, monocytes were significantly lower in patients with DF compared to patients with malaria (P < 0.005). In contrast, lymphocytes, red blood cells, hemoglobin, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration were significantly higher in patients with DF as compared to patients with malaria (P < 0.005). Conclusion This study concludes that hematological parameters differ in Dengue Fever and Malaria,and using these parameters- haemoglobin, PCV, RBC, total count, neutrophils, lymphocytes, monocytes, eosinophils, platelets, MCV, MCH, MCHC, age and gender, we can discriminate patients with dengue and malaria infection. In addition, using these parameters, will lead to early detection, diagnosis, and managementt of these tropical diseases.